The economics of fleet management computing. - Paulits, Jim (American City & County, 1996)
A comparison of the benefits of client/server computing and host-centric computing systems in the management of a city's fleet. The advantages of the client/server computing system are its powerful distributed processing abilities, the familiarity of its Windows environment, and the ease with which users can transfer between software applications running on their desktop computer. However, the host-centric system, as was adopted by Los Angeles last year, is less expensive and more durable than the client/server option and will remain as an alternative choice for some cities.